2023
DOI: 10.1111/sms.14444
|View full text |Cite
|
Sign up to set email alerts
|

Triceps surae muscle forces during dynamic exercises in patients with Achilles tendinopathy: A cross‐sectional study

Abstract: PurposeThe aim of this study was to investigate the individual triceps surae muscle forces during the execution of six different functional movements and rehabilitation exercises in patients with Achilles tendinopathy compared to a control group.MethodsTriceps surae muscle forces of 15 participants with Achilles tendinopathy (AT) and 15 healthy controls were estimated through a combination of experimental data and musculo‐skeletal modeling. Three‐dimensional motion capture and force plates were used to collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Moreover, our results highlight the importance of physiotherapists providing clear instructions and feedback about the performed exercises as small differences in knee and ankle angles can result in altered loading of the Achilles tendon. Additionally, our results and previous research (43) suggested that during daily activities such as walking, the Achilles tendon already undergoes a considerable amount of peak loading, yet with a lower loading rate. Therefore, it seems important to better account for this daily cumulative load during the rehabilitation.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Moreover, our results highlight the importance of physiotherapists providing clear instructions and feedback about the performed exercises as small differences in knee and ankle angles can result in altered loading of the Achilles tendon. Additionally, our results and previous research (43) suggested that during daily activities such as walking, the Achilles tendon already undergoes a considerable amount of peak loading, yet with a lower loading rate. Therefore, it seems important to better account for this daily cumulative load during the rehabilitation.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, our results and previous research (43) suggested that during daily activities such as walking, the Achilles tendon already undergoes a considerable amount of peak loading, yet with a lower loading rate. Therefore, it seems important to better account for this daily cumulative load during the rehabilitation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In line with previous results (Hansen et al, 2017; Shim et al, 2019), it becomes evident that when creating subject-specific models, prioritizing not only subject-specific geometry but also subject-specific muscle forces over material properties, is crucial for a more accurate representation of the AT strains, especially when considering Achilles tendinopathy patients. Mylle et al . (2023) demonstrated a different force distribution strategy between Achilles tendinopathy patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the differential force exerted by the triceps surae muscles plays a crucial role in the elongations of the sub-tendons, subsequently the strains in the AT. In individuals with Achilles tendinopathy, there is a noticeable change in the force distribution strategies employed by the triceps surae muscles during dynamic tasks (Mylle et al, 2023). Consequently, it becomes pivotal to consider the impact of triceps surae muscle forces on AT when examining the factors contributing to strain development in patients with Achilles tendinopathy.…”
Section: Introductionmentioning
confidence: 99%